2017
DOI: 10.1111/hdi.12586
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation and clotting cascade activation by dialyzers designed for high volume online hemodiafiltration

Abstract: Despite being pro-thrombotic, with activation of platelets, and lymphocytes during passage through ECC, no macroscopic clotting, or increased TATs were noted during OL-HDF, and no major differences between cellulosic and polysulphone dialyzers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 33 publications
1
23
1
Order By: Relevance
“…The study of Tangvoraphonkchai et al showed that dialyzer membranes, designed for high volume on‐line HDF, allow the achievement of high‐volume exchanges without an increased risk of ECC clotting and, no major differences between cellulosic and polysulfone dialyzers were found. There was no increase in microparticles, PF4, or thrombin antithrombin complexes (TATs) . In recent reports, the biocompatibility of the dialyzer membranes was monitored by the platelet count and it was concluded that the more biocompatible newer membranes, like the polysulfones, do not result in marked thrombocytopenia .…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The study of Tangvoraphonkchai et al showed that dialyzer membranes, designed for high volume on‐line HDF, allow the achievement of high‐volume exchanges without an increased risk of ECC clotting and, no major differences between cellulosic and polysulfone dialyzers were found. There was no increase in microparticles, PF4, or thrombin antithrombin complexes (TATs) . In recent reports, the biocompatibility of the dialyzer membranes was monitored by the platelet count and it was concluded that the more biocompatible newer membranes, like the polysulfones, do not result in marked thrombocytopenia .…”
Section: Discussionmentioning
confidence: 60%
“…However, this potentially allows a greater change in hydrostatic pressure to occur as blood passes through the dialyzer and changes in pressure, and flow patterns may potentially lead to increased platelet and leukocyte activation and increase the risk of clotting in the extracorporeal circuit (ECC). 19 The study of Tangvoraphonkchai et al showed that dialyzer membranes, designed for high volume on-line HDF, allow the achievement of high-volume exchanges without an increased risk of ECC clotting and, no major differences between cellulosic and polysulfone dialyzers were found. There was no increase in microparticles, PF4, or thrombin antithrombin complexes (TATs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, although dialyzers designed for diffusion traditionally have very narrow internal fiber diameters to minimize the distance for diffusion, designed to increase diffusive clearance, narrow diameter fibers potentially increase the risk of haemoconcentration and clotting when used for haemodiafiltration. So, high‐flux dialyzers designed for haemodiafiltration have wider internal diameter fibers …”
Section: Haemodiafiltrationmentioning
confidence: 99%
“…So, high-flux dialyzers designed for haemodiafiltration have wider internal diameter fibers. 20 In pediatric practice, blood flows are generally much slower than in adult practice, and as such pre-dilutional haemodiafiltration is the more commonly performed. Pre-dilution reduces haemoconcentration, and although in theory would allow greater convective clearances, in clinical practice the removal of larger solutes such as alpha-1 macroglobulin do not differ between pre-and post-dilution modes, due to increased membrane adsorption with the post-dilution mode.…”
Section: Haemodiafiltrationmentioning
confidence: 99%